The involvement of young people in school- and community-based noncommunicable disease prevention interventions: a scoping review of designs and outcomes - Didier Jourdan; Julie Hellesøe Christensen; Emily Darlington; Ane Høstgaard Bonde; Paul Bloch; Bjarne Bruun Jensen; Peter Bentsen (BMC, 2016)
Abstract Background Since stakeholders' active engagement is essential for public health strategies to be effective, this review is focused on intervention designs and outcomes of school- and community-based noncommunicable disease (NCD) prevention interventions involving children and young people. Methods The review process was based on the principles of scoping reviews. A systematic search was conducted in eight major databases in October 2015. Empirical studies published in English, French, Portuguese, and Spanish were considered. Five selection criteria were applied. Included in the review were (1) empirical studies describing (2) a health intervention focused on diet and/or physical activity, (3) based on children's and young people's involvement that included (4) a relationship between school and local community while (5) providing explicit information about the outcomes of the intervention. The search provided 3995 hits, of which 3253 were screened by title and abstract, leading to the full-text screening of 24 papers. Ultimately, 12 papers were included in the review. The included papers were analysed independently by at least two reviewers. Results Few relevant papers were identified because interventions are often either based on children's involvement or are multi-setting, but rarely both. Children were involved through participation in needs assessments, health committees and advocacy. School-community collaboration ranged from shared activities, to joint interventions with common goals and activities. Most often, collaboration was school-initiated. Most papers provided a limited description of the outcomes. Positive effects were identified at the organisational level (policy, action plans, and healthy environments), in adult stakeholders (empowerment, healthy eating) and in children (knowledge, social norms, critical thinking, and health behaviour). Limitations related to the search and analytical methods are discussed. Conclusion There are very few published studies on the effectiveness of interventions based on children's involvement in school- and community-based NCD prevention programmes. However, interventions with these characteristics show potential benefits, and the merits of complex multi-setting approaches should be further explored through intervention-based studies assessing their effectiveness and identifying which components contribute to the observed outcomes.